Experimental demonstration of optimized quantum process tomography on the IBM quantum experience - Gaikwad, Akshay; Shende, Krishna; Dorai, Kavita (World Scientific, 2021)
We experimentally performed complete and optimized quantum process tomography of quantum gates implemented on superconducting qubit-based IBM QX2 quantum processor via two constrained convex optimization (CCO) techniques: least squares optimization and compressed sensing optimization. We studied the performance of these methods by comparing the experimental complexity involved and the experimental fidelities obtained. We experimentally characterized several two-qubit quantum gates: identity gate, a controlled-NOT gate, and a SWAP gate. The general quantum circuit is efficient in the sense that the data needed to perform CCO-based process tomography can be directly acquired by measuring only a single qubit. The quantum circuit can be extended to higher dimensions and is also valid for other experimental platforms.
Only IISERM authors are available in the record.
Keywords: Experimental; demonstration; optimized; quantum